2020
DOI: 10.3390/ijms21218003
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Soil Microbiome as Affected by the Application of Phosphorus Biofertilizer: Fertilizer Enriched with Beneficial Bacterial Strains

Abstract: Regarding the unfavourable changes in agroecosystems resulting from the excessive application of mineral fertilizers, biopreparations containing live microorganisms are gaining increasing attention. We assumed that the application of phosphorus mineral fertilizer enriched with strains of beneficial microorganisms contribute to favourable changes in enzymatic activity and in the genetic and functional diversity of microbial populations inhabiting degraded soils. Therefore, in field experiments conditions, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 156 publications
(153 reference statements)
5
20
0
Order By: Relevance
“…The addition of microorganisms or NPK did not cause significant changes or a clear uniform trend during experiment period in HAs from BA soil, which likely resulted from the differences in the physicochemical properties of BA soil in relation to AL. This is in line with the conclusions of Mącik et al [ 33 ] regarding the different effects of microbial communities on enzymatic activity, and the genetic and functional diversity of BA and AL soils.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The addition of microorganisms or NPK did not cause significant changes or a clear uniform trend during experiment period in HAs from BA soil, which likely resulted from the differences in the physicochemical properties of BA soil in relation to AL. This is in line with the conclusions of Mącik et al [ 33 ] regarding the different effects of microbial communities on enzymatic activity, and the genetic and functional diversity of BA and AL soils.…”
Section: Resultssupporting
confidence: 92%
“…It should be noted, however, that the strains of microorganisms proposed in our research show beneficial, biological effects in the soils tested, which was confirmed by our previous studies. Mącik et al [33] observed the increase of amino acids metabolism in BA soil after addition of phosphorus fertilizers enriched with the same strains used in current study as compared to the control soil with mineral fertilization. The above authors showed also that mineral fertilization supplemented to the soil together with the bacterial strains provided positive effect on the microbiome changes and genetic biodiversity in soil.…”
Section: Agronomic Implications and Further Researchsupporting
confidence: 57%
See 2 more Smart Citations
“…Many species possess the ability to accelerate the organic compound transformation and fatty acids production [74]. Moreover, it was found that Mortierellales representatives increased in treatments fertilized with phosphorus biofertilizer [75]. The class of fungi which decreased after SMS and CM addition to the soil was Dothideomycetes, which is involved in the decay of cell walls [14] and is important in biomass degradation, and as the saprophyte is engaged in carbon cycling [76].…”
Section: Effects Of the Organic Additives On The Soil Fungal Community Structurementioning
confidence: 99%